EL GÉNERO FIDENA WALKER 1850 EN ARGENTINA Y CHILE (DIPTERA: TABANIDAE) - Coscaron, S. (Acta Entomológica Chilena, 2022)
The genus Fidena inelude 86 species, 10 of them live in Argentina of which F. atripes and F. m o ñ o are in common with Chile. The following subgenera F. (Fidena) species: abominata, Philip 9» Cf, atripes (von Roeder) 9. latifrons Kroeber 9, Cf, longipalpis Enderlein 9» C?, neglecta Kroeber 9, Cf, nigripes (von Roeder) 9. Cf, ochrapogon Wilkerson 9, opaca (Bréthes) 9, CF, sorhens Wiedemann 9, Cf, and from subgenera F. (Leptofídena) haywardi Philip 9 and moño van der Wulp 9, Cf, are redescribed; illustrations, geographic distribution and female keys are included. A new species Fidena philipi (9) is described; F. atripes, latifrons, neglecta, nigripes and ochrapogon are for the first time mentioned for Argentina; the males described were unknown before.